2019
DOI: 10.1558/isla.38247
|View full text |Cite
|
Sign up to set email alerts
|

Beginning L2 complexity development in CLIL and non-CLIL secondary education

Abstract: The present study analyses the impact of a bilingual Content and Language Integrated Learning (CLIL) programme vis-à-vis a regular monolingual programme on the development of different aspects of L2 learners’ linguistic (syntactic, morphological and lexical) complexity. Five pupils enrolled in a Dutch–English CLIL programme in a secondary school in the Netherlands are compared with five peers following the mainstream programme with English as a Foreign Language (EFL) teaching. The longitudinal development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…Following previous L2 writing studies and small-scale L2 spoken studies, we found that number of types, TTR, and Root TTR are strongly and intrinsically related to text length in oral proficiency interview settings. Although these results are not surprising given previous research, it bears repeating that Root TTR conflates lexical diversity and text length given the fact that it continues to be used as an index of lexical diversity in SLA research (Bulté & Housen, 2019;Lambelet, 2021). This study also found that D is moderately and intrinsically related to text length (r = .505) in oral proficiency contexts.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Following previous L2 writing studies and small-scale L2 spoken studies, we found that number of types, TTR, and Root TTR are strongly and intrinsically related to text length in oral proficiency interview settings. Although these results are not surprising given previous research, it bears repeating that Root TTR conflates lexical diversity and text length given the fact that it continues to be used as an index of lexical diversity in SLA research (Bulté & Housen, 2019;Lambelet, 2021). This study also found that D is moderately and intrinsically related to text length (r = .505) in oral proficiency contexts.…”
Section: Discussionsupporting
confidence: 71%
“…An early attempt to mitigate this relationship was to transform the TTR value by using the square root of the number of tokens in the denominator (Guiraud, 1960). Although this index, commonly referred to as Root TTR or Guiraud’s index, gained a reputation as an appropriate substitute for TTR and is still used fairly widely (Bulté & Housen, 2019; Lambelet, 2021), studies have repeatedly shown that it strongly overcorrects TTR’s negative relationship with text length (e.g., Koizumi & In’nami, 2012; McCarthy & Jarvis, 2010; Zenker & Kyle, 2021). One possible reason for the durability of Root TTR in the field is that it tends to demonstrate a relatively strong relationship with proficiency, and it is certainly an improvement over TTR because it is positively correlated with text length and therefore does not penalize longer essays (see Bulté & Roothooft, 2020; Treffers-Daller et al, 2018).…”
Section: Lexical Diversity Indices and Text-length Stabilitymentioning
confidence: 99%
“…The fact that students grew up speaking Spanish in their homes but had only been taught writing through the medium of instruction, English, was brought to the fore as an explanation of the higher fluency in English (Mikulski & Elola, 2011). Somewhat contradictory results are presented in Bulté and Housen (2019), who found only limited effects of English (L2) as a medium of instruction in a high exposure CLIL (Content and Language Integrated Learning) program on 11-13 years-old children's L2 written complexity. Thus, even though exposure to the L2 target language has an effect on children and adults' L2 proficiency, evidence seems more consistent regarding aspects of reading, listening and vocabulary, than speaking and indeed, writing.…”
Section: Exposure L2 Development and Fluencymentioning
confidence: 99%